Syntheses of block trimethylene carbonate/?-caprolactone copolymers via coupling of corresponding polyester diols with diisocyanates - Łukaszczyk, J.; Jelonek, P.; Trzebicka, B. (Polimery, 2022)
Series of block copolymers of ?-caprolactone (CL) and trimethylene carbonate (TMC) [poli(?-CL-b-TMC)], differing in molecular weights, were synthesized. The copolymers were obtained by coupling of dihydroxyl compounds using diisocyanates as chain extenders [hexamethylene diisocyanate (HDI), dicyclohexylmethane 4,4’-diisocyanate (CHMDI) or isophorone diisocyanate (IPDI)] in the presence of dibutyltin laurate (DBTL) as a catalyst. Commercial poly(?-caprolactone) diol (PCLdiol) and poly(trimethylene carbonate with hydroxyl end-groups) obtained by authors, in the process of coordination polymerization catalyzed with stannous 2-ethylhexanoate and initiated with triethylene glycol (TEG) [equation (1), Fig. 1], were used as dihydroxyl compounds. The use of HDI let obtain the highest molecular weight of copolymer (Table 1), however, the formation of insoluble products was observed. In case of CHMDI or IPDI the insoluble products were formed and molecular weights of copolymers were lower. Two thermal transitions [glass transition (Tg) related to PTMC fragment, and melting point (Tm) related to PCL fragment] are present at DSC thermograms (Fig. 5). However, these thermograms do not let determine the miscibility degree of the blocks unequivocally. The chemical structures of intermediate (PCLpre) and final products were confirmed by 1H NMR (Fig. 2 and 4), 13C NMR and IR (Fig. 3). The results of molecular weights and polydispersity determinations (Table 1-3) were also given.